PENGARUH KECERDASAN EMOSI DAN KOMITMEN ORGANISASI TERHADAP OCB (ORGANIZATIONAL CITIZENSHIP BEHAVIOR) DI RSU PKU MUHAMMADIYAH BANTUL - Febri Inawati (2013)

(untitled)
RSU PKU Muhammadiyah Bantul is a service provider organization that must be supported with adequate human resource and quality; increasing the factor of emotional intelligence and commitment of employees of the organization should support this. This study aimed to determine (1) the influence of emotional intelligence and organizational citizenship behavior (OCB); (2) the employee's commitment with OCB; (3) the influence of emotional intelligence and commitment of employees at the OCB PKU Muhamma